Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) XI. The rubra species-group and the fuscimacularis species-group, with descriptions of six new species - Wang, Shuxia; Liu, Chen (Zootaxa, 2021)
The rubra and the fuscimacularis species-groups of the genus Promalactis Meyrick, 1908 are proposed for the first time based on the forewing patterns. Moths of the rubra species-group are characterized by the ochreous forewing of all shades with a short dorsal spot or a short obliquely inward dorsal streak; moths of the fuscimacularis species-group are characterized by the forewing having a dark basal spot or a dark basal costal patch. Six species are described as new: P. albimarginalis Wang, sp. nov., P. introextensa Wang, sp. nov., P. magnisticta Wang, sp. nov., P. anteromacularis Wang, sp. nov., P. fuscimacularis Wang, sp. nov., P. folivalvaris Wang, sp. nov. Photographs of adults and genitalia of the new species are provided. A list of species belonging to both species-groups is given.